2008
DOI: 10.1007/s11259-008-9168-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of insulin signaling gene expression in insulin sensitive tissues between cats and dogs

Abstract: Diabetes mellitus (DM) is a common endocrine disease in cats and dogs with increasing prevalence. Type 1 DM appears to be the most common form of diabetes in dogs whereas Type 2 DM prevails for cats. Since insulin resistance is more frequently encountered in cats than dogs, our laboratory was interested in determining whether differences at the insulin signaling pathway level and differences in glucose and lipid metabolism could be observed between cats and dogs. Insulin resistance has been positively correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Similarly, Mori et al (2009) reported that MDH1 mRNA is highly expressed in skeletal muscle in cats. We confirmed the high expression level of MDH1 in feline heart and skeletal muscle and determined that MDH2 is also expressed at high levels in heart and skeletal muscle.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, Mori et al (2009) reported that MDH1 mRNA is highly expressed in skeletal muscle in cats. We confirmed the high expression level of MDH1 in feline heart and skeletal muscle and determined that MDH2 is also expressed at high levels in heart and skeletal muscle.…”
Section: Discussionmentioning
confidence: 84%
“…Even though inter-species differences in enzyme activities have to be interpreted with caution, it seems that cats may be less insulin sensitive than dogs because the expression of genes involved in glucose and lipid metabolism is lower in insulin-sensitive tissues in cats than in dogs (Mori et al, 2009a;Mori et al, 2009b). Nonetheless, and similar to dogs, obese cats have an increased expression of lipid and carbohydrate metabolism-related genes compared to their lean counterparts (Brennan et al, 2004;Mori et al, 2009b).…”
Section: Dogs and Catsmentioning
confidence: 99%
“…Nonetheless, and similar to dogs, obese cats have an increased expression of lipid and carbohydrate metabolism-related genes compared to their lean counterparts (Brennan et al, 2004;Mori et al, 2009b).…”
Section: Dogs and Catsmentioning
confidence: 99%
“…In particular, IRS-1, IRS-2 and PI3-K P-85 are important downstream players of insulin [59] and have been implicated with the incidence of insulin resistance and DM [22,28,48]. They are expressed in insulin-sensitive tissues such as the liver, skeletal muscle, abdominal fat and peripheral leukocytes [33,34].…”
mentioning
confidence: 99%
“…Previously, our laboratory demonstrated that leukocytes can be used to indirectly monitor changes in certain insulinsensitive tissues depending on what marker is utilized [34]. Leukocytes are usually used in clinical studies on insulin action because they are 1) insulin target cells and 2) easy to access as opposed to other insulin-sensitive tissues.…”
mentioning
confidence: 99%